From leadership humility to customer satisfaction: a study of employee engagement in the Chinese service industry - Zhang, Xinyang; Yim, Sanghyuk (Frontiers in Psychology, 2025)
PurposeThe study proposes to integrate Leader-Member Exchange (LMX) and Self-Determination Theory (SDT) to study Humble Leadership (HL) impact on Employee engagement, Service Performance and Customer satisfaction in the Chinese service industry.Design/methodology/approachA quantitative approach used purposive sampling, including 485 participants from organizations in the Chinese service industry. The data was further processed and tested through a PLS-SEM procedure to check the hypothesized relationships.FindingsResults of the study prove that leadership humility (LHU; β = 0.224, p < 0.001), relational empowerment (REM; β = 0.186, p < 0.001), and psychological safety (PSA; β = 0.138, p = 0.003) could be identified as critical antecedents of employee engagement (EEN). Additionally, autonomy support (AUS; β = 0.135, p = 0.001), competence development (CDE; β = 0.345, p < 0.001), and relatedness fulfillment (REF; β = 0.126, p < 0.001) significantly influence engagement positively. Moreover, employee engagement (β = 0.757, p < 0.001) has a profound impact on service performance, which in turn dramatically affects customer satisfaction (β = 0.477, p < 0.001). The study confirms employee engagement (β = 0.406, p < 0.001) as a driver of service performance and customer satisfaction within the service industry context.Practical implicationsThe study results propose practical suggestions for managers and leaders in the service industry as Organizations should develop humble leadership behaviors, empowering, and creating psychological safety while satisfying employees’ needs for autonomy, competence, and relatedness.Originality/valueThe study helps in defining humble leadership as it integrates LMX and SDT frameworks in the context of the Chinese service industry. The study thus provides empirical evidence as to how humble leadership and employee engagement jointly work in the direction of better service performance and customer outcomes, consequently contributing to the literature on both leadership and service management.